Enhanced and stable photoelectrochemical H2 production using a engineered nano multijunction with Cu2O photocathode - Kalanur, Shankara S.; Lee, Young Jae; Seo, Hyungtak (Materials Today Chemistry, 2022)
Cuprous oxide (Cu2O) is one of the ideal photocathodes explored for solar water splitting applications due to its suitable optical properties and band edge positions. However, state-of-the-art Cu2O employs Au back contact for hole extraction and Pt or Ru catalyst for water reduction reactions. Moreover, photo-corrosion of Cu2O during the AM 1.5 G illumination is one of the serious challenges that limit the efficiency of water splitting reactions. In this work, a multijunction strategy in which the Cu2O is sandwiched between the stoichiometrically engineered hole extraction layer and an efficient, non-toxic MoOx catalyst layer is proposed for the enhanced charge separation and stable H2 production activity. The optimized multijunction system exhibits the highest photocurrent of 6.1 mA cm−2 at 0 V vs RHE reported for noble metal-free Cu2O photocathodes. Furthermore, a significant anodic shift in onset potential was noticed. In the multijunction, the tuned layers of NiOx, aluminum-doped zinc oxide, and MoOx act as hole scavenger, electron tunneler, and H2 catalyst, respectively. Importantly, the proposed nanolayers multijunction system demonstrates the effective utilization of noble metal and sulfide-free components for stable and enhanced H2 productions employing Cu2O photocathodes.
Keywords: Band edge position; H 2 production; Hole extractions; MoOx; Multi-junctions; NiOx; Optical bands; Photoelectrochemical water splitting; Photoelectrochemicals; Solar water splitting; Hole extraction; MoOx; NiOx; Photocathode; Photoelectrochemical water splitting